2020
DOI: 10.1111/codi.15338
|View full text |Cite
|
Sign up to set email alerts
|

Perineal stapled prolapse resection for external rectal prolapse: a systematic review and meta‐analysis

Abstract: Aim Rectal prolapse is an uncommon but debilitating pelvic floor disorder that significantly decreases the quality of life of affected patients. Perineal stapled prolapse resection is a relatively new perineal approach that offers an promising alternative technique in the surgical management of rectal prolapse. It appears to be a simple, reproducible and efficient method. However, longterm outcomes are limited. The aims of this review are to assess the safety and effectiveness of perineal stapled prolapse rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…Scherer et al reported that, in 14 of 15 patients (93%), perineal stapled prolapse resection was successfully performed without complications, and the median operating time was 33 min (range: 22–52 min) [ 11 ]. Fan et al reported that, in a systematic review of 408 patients who underwent perineal stapled prolapse resection, bleeding was the most common complication, and the total complication rate was 14.5% (51/350) [ 12 ]. However, in a recent systematic review, the median incidence of recurrence was 13.9% for perineal stapled prolapse resection, which was higher than that of the Altemeier procedure (11.4%) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scherer et al reported that, in 14 of 15 patients (93%), perineal stapled prolapse resection was successfully performed without complications, and the median operating time was 33 min (range: 22–52 min) [ 11 ]. Fan et al reported that, in a systematic review of 408 patients who underwent perineal stapled prolapse resection, bleeding was the most common complication, and the total complication rate was 14.5% (51/350) [ 12 ]. However, in a recent systematic review, the median incidence of recurrence was 13.9% for perineal stapled prolapse resection, which was higher than that of the Altemeier procedure (11.4%) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…It appears to be a technically simple, reproducible and efficient method. However, there are limited published data on its long term clinical outcomes and failure rates [2], and the recurrence rate is comparable to other well-established techniques such as Altemeier's and Delorme's procedures [1,4].…”
Section: Perineal Stapled Prolapse Resection (Pspr) For Full Thicknes...mentioning
confidence: 94%
“…External rectal prolapse is a rare condition, which is more common in older and multi-morbid women with a debilitating pelvic floor disorder that significantly decreases the quality of life of affected patients [1,2]. The estimated adult prevalence of rectal prolapse is 1% in those aged 65 years and greater [1].…”
Section: Perineal Stapled Prolapse Resection (Pspr) For Full Thickness External Large Rectal Prolapse In a Frail Elderly Patient; An Easymentioning
confidence: 99%
See 1 more Smart Citation
“…Perineal procedures are often reserved for those patients presenting with FTRP who are elderly or who have significant comorbidities [14]. Alternative approaches have included the Delorme mucosectomy, Altemeier's perineal rectosigmoidectomy, and more recently, stapled prolapse resection [15][16][17]. We report the outcomes of a cohort of patients presenting with FTRP who were managed with a transanal sacral rectopexy supplemented by ultrasonographically-guided sclerosant (sodium tetradecyl sulfate plus polidocanol) injected into the retrorectal space.…”
mentioning
confidence: 99%